Stream nitrogen uptake associated with suspended sediments: A microcosm study - Bacmeister, Eva; Peck, E.; Bernasconi, S.; Inamdar, S.; Kan, J.; Peipoch, M. (Frontiers in Environmental Science, 2022)
Despite significant advances in our understanding of nitrogen (N) removal pathways along river networks, the role of water column processes remains largely understudied. This knowledge gap not only limits our capacity to determine N transport and retention in mid-to-large rivers, but it also hampers our understanding of N removal processes in smaller streams during stormflow conditions, in which significant increases in suspended sediment concentrations (SSC) typically occur. High SSC in the water column can provide abundant substrate for microbial growth and water column N uptake. However, storms of different size mobilize different quantities of sediment of varying properties and sizes, which can ultimately modulate water column N uptake rates in the stream during stormflows. To assess water column N uptake associated with suspended sediment particles of different sources and sizes, we quantified assimilatory and dissimilatory N uptake rates in a set of microcosms representing a gradient of sediment properties (organic matter, N content, and microbial activity) and surface area (fine vs. coarse size) availability. Water column assimilatory uptake (Used) ranged from 12.7 to 187.8 µg N [g sediment]-1 d-1 across all sediment sources and size fractions, and was higher on average than denitrification rates (DNsed) in agricultural and stream bank sediments but not in streambed sediments (mean DNsed = 240.9 ± 99 µg N [g sediment]-1 d-1). Sediment-bound C in suspended sediment varied among sediment sources and was directly related to Used rates, but not to DNsed rates, which were less predictable and more variable. Overall, our results showed a positive nonlinear relationship between water column N uptake and SSC, while indicating that water column N uptake may scale differently to SSC depending on sediment source, and to a lesser degree, particle size. Because low, moderate, and large storms can mobilize different quantities of sediment in the watershed of different sources and sizes, it is likely that storm size will ultimately modulate the contribution of water column uptake during storm events to whole-reach N retention.